2012
DOI: 10.1149/1.3703509
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Oxide with Different Oxygen Contents as Photocatalysts for Hydrogen and Oxygen Evolution from Water

Abstract: Graphite oxide (GO) photocatalysts were derived from graphite oxidation. Absorption spectroscopy shows the increasing band gap of GO with the oxygen content. Electrochemical analysis along with the Mott-Schottky equation show that the conduction and valence band edge levels of GO from appropriate oxidation are suitable for both the reduction and oxidation of water. The photocatalytic activity of GO specimens with various oxygen contents was measured in methanol and AgNO 3 solutions for H 2 and O 2 evolution, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…This indicated that the bandgap energies for TiO 2 @ CoO-doped GO and TiO 2 @NiO-doped GO are lower than that of anatase TiO 2 . This finding is agreement with previously stated [14]. It was presence of transition the p-type metal oxide on GO sheet forms a heterojunction with n-type TiO 2 which generates the synergistic effect via promoting the extension of electron/hole lifetime due to difference Fermi levels.…”
Section: Resultssupporting
confidence: 93%
“…This indicated that the bandgap energies for TiO 2 @ CoO-doped GO and TiO 2 @NiO-doped GO are lower than that of anatase TiO 2 . This finding is agreement with previously stated [14]. It was presence of transition the p-type metal oxide on GO sheet forms a heterojunction with n-type TiO 2 which generates the synergistic effect via promoting the extension of electron/hole lifetime due to difference Fermi levels.…”
Section: Resultssupporting
confidence: 93%
“…Several research articles have reported higher photocatalytic activity and faster reaction rates when GO/rGO-modified TiO 2 photocatalysts were used for organic pollutant photodegradation, dye photoremoval, bacterial inactivation and H 2 production [30][31][32][33][34]. Depending on the reduction degree of GO the valence band and conduction band position are shifted, which means that when oxygen content in GO is high enough GO could even act as a photocatalyst or a photosensitizer [35,36]. Therefore, it is crucial to know the role played by rGO in TiO 2 -graphene nanocomposites since depending on the bands position and the excitation wavelength, the photocatalytic process can take place by different mechanisms, for example, electrons could be transferred from TiO 2 to rGO or vice versa [28].…”
Section: Introductionmentioning
confidence: 99%